Investigation of potential biomarkers for the early diagnosis of cellular stability after the exposure of agricultural workers to pesticides - ALVES,JODEL S. (2016)
ABSTRACT Agricultural workers involved in the harvest of tobacco crops are regularly exposed to large quantities of pesticides. In order to determine how this exposure to pesticides induces genetic alterations in these workers, blood samples were obtained from 77 exposed individuals, as well as from 60 unexposed subjects. DNA damage was analyzed by the Comet assay and by the micronucleus (MN) test. The antioxidant profile was evaluated by activity of superoxide dismutase (SOD), and the polymorphism of gene PON1 was used as a susceptibility biomarker. The content of inorganic elements in the blood samples was determined by PIXE analysis. Our results demonstrated that the damage frequency, damage index, the MN frequency, and the SOD activity were significantly elevated in the exposed relative to the unexposed group. A modulation of the MN results for the PON1 gene was observed in the exposed group. The concentrations of inorganic elements in the exposed group were higher compared to those of the unexposed group. In this study, we observed that genetic damage, and change in oxidative balance were induced by the exposure of workers to complex mixtures of pesticides in the presence of inorganic compounds, whereby an influence of the genotype was evident.